Long term psychosocial outcomes of congenital heart disease (CHD) in adolescents and young adults - Areias, Maria (2013)
Background: Congenital heart disease (CHD) is a chronic illness with a high frequency in the worldwide population, and is normally diagnosed at birth or in uterus. Because of better conditions in diagnosis and early medical and surgical treatment, patients have survival rates of 90% and go further and further in life, facing different challenges in life cycle. In this study, we tested the effects of different demographic, clinical and psychosocial variables on the perception of quality of life (QOL), on psychosocial adjustment (PSA) and psychiatric morbidity (PM) of adolescents and young adults with CHD. Objectives: We aimed to evaluate QOL, PM and PSA of adolescents and young adults with CHD and to determine which variables (demographic, clinical, and psychosocial) play a role in buffering stress and promoting resilience and which ones have a detrimental effect. Methods: The study enrolled 150 CHD patients (87 males and 63 females), 12 to 26 years (M: 17.45± 3.373 years). The participants were interviewed regarding social support, family educational style, self-image, demographic information and physical limitations. They responded to questions in a standardized psychiatric interview (SADS-L) and completed self-reports questionnaires for assessment of QOL (WHOQOL-BREF) and PSA (YSR/ASR). Results: We found an 18.7% lifetime prevalence of psychopathology in our participants (25.4% in females and 13.8% in males). 57.1% had retentions in school (M: 1.53±0.804 year). The perception of QOL of CHD patients is better compared to the Portuguese population in the Social Relationships, Environmental, Physical and General Dimensions. However, it is worse in complex forms of CHD, in cyanotic patients, in moderate-to-severe residual lesions, in patients submitted to surgery and in patients with physical limitations. All of these variables, except presence of cyanosis, are also associated to a worse PSA. Social Support is very important in improving QOL of patients in all dimensions as well as academic performance. Conclusions: Female patients and patients with poor academic performance and poor social support refer worse PSA and QOL. Key Words: Congenital heart disease (CHD); risk factor; quality of life (QOL); psychosocial adjustment (PSA); psychiatric morbidity (PM)